Determination and modeling of binary and ternary solid-liquid phase equilibrium for the systems formed by 3, 5-dinitrobenzoic acid, m-nitrobenzoic acid and acetone. (February 2017) - Li, Xinbao; Du, Cunbin; Zhao, Hongkun
Graphical abstract: Highlights: The solubility of 3, 5-dinitrobenzoic acid in acetone was determined. Solubility of m -nitrobenzoic acid + 3, 5-dinitrobenzoic acid + acetone was determined. Three ternary phase diagrams were constructed for the ternary system. The ternary phase diagrams were calculated by Wilson model and NRTL model. Abstract: The solubility of 3, 5-dinitrobenzoic acid in acetone at the temperatures ranging from (283.15 to 318.15) K and the mutual solubility of the ternary m -nitrobenzoic acid + 3, 5-dinitrobenzoic acid + acetone system at (283.15, 298.15 and 313.15) K were determined experimentally by using the isothermal saturation method under atmosphere pressure (101.2 kPa). Three isothermal ternary phase diagrams were constructed according to the measured mutual solubility data. In each ternary phase diagram, there was one co-saturated point, two boundary curves, and three crystalline regions. The modified Apelblat equation, λh equation, NRTL model and Wilson model were used to correlate the solubility of 3, 5-dinitrobenzoic acid in acetone; and the NRTL and Wilson models, the mutual solubility for the ternary m -nitrobenzoic acid + 3, 5-dinitrobenzoic acid + acetone system. The value of root-mean-square deviation ( RMSD ) was 8.53 × 10 −4 for the binary system of 3, 5-dinitrobenzoic acid + acetone; and the largest value of RMSD was 81.08 × 10 −4 for the ternary system.